Penyelesaian Sengketa Pertanahan melalui Hukum Perdata: Dari Konstruksi Gugatan hingga Implikasi Putusan - Atis Ika Ernawati; Muhammad Awaluddin; Miftahuddin Miftahuddin; Hajairin Hajairin (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This research This study aims to analyze the role of civil law in resolving land disputes by emphasizing three main aspects: the construction of lawsuits, evidence, and the implications of court decisions. The focus of the study is directed at how these three aspects are interrelated in providing legal certainty while also ensuring substantive justice for the disputing parties. This article falls under qualitative library research. The methodology applied is a juridical-normative study by examining legislation, legal doctrines, and jurisprudence related to land disputes. The resolution of land disputes through civil law highlights the importance of lawsuit construction, evidence, and court decisions as interdependent stages. Clear lawsuits and consistent evidence serve as the basis for judges to balance legal formalism with substantive justice. Court decisions have broad implications, not only for the legal certainty of land ownership but also for public trust in the legal system and social stability.